Composition for photovoltaic glass, photovoltaic glass as well as preparation method and application of photovoltaic glass

By accurately controlling the ratio of oxides in photovoltaic glass and using specific composite clarification agents, the problems of poor clarification effect and high melting temperature of photovoltaic glass are solved, and higher transmittance and lower energy consumption are achieved.

CN119841551APending Publication Date: 2025-04-18TUNGHSU TECH GRP CO LTD

Patent Information

Application Number
CN202411790136.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing photovoltaic glass has poor clarification effect and high melting temperature, resulting in increased production costs and poor glass quality.

Method used

By accurately controlling the ratio of SiO2, Al2O3, CaO, MgO, K2O and Na2O, and using a combined composite clarifier of potassium hydrogen fluoride, potassium nitrate, sodium pyromotivenate, sodium sulfate and carbon powder, the clarification effect of photovoltaic glass and the melting temperature are improved.

Benefits of technology

It significantly improves the clarification effect and transmittance of photovoltaic glass, while reducing the melting temperature of the glass, reducing energy consumption and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175118350000111
    Figure BDA0005175118350000111
  • Figure BDA0005175118350000121
    Figure BDA0005175118350000121
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic glass, and discloses a composition for photovoltaic glass, the photovoltaic glass and a preparation method and application of the photovoltaic glass. Based on the total weight of the composition, the composition is prepared from the following components in percentage by weight: 65 to 75 percent of SiO2, 0.5 to 0.9 percent of Al2O3, 13 to 15 percent of Na2O, 0.02 to 0.2 percent of K2O, 9 to 12 percent of CaO, 2 to 5 percent of MgO and 0.2 to 0.9 percent of compound clarifying agent, the composite clarifying agent is a combination of potassium bifluoride, potassium nitrate, sodium pyroantimonate, sodium sulfate and carbon powder. The photovoltaic glass prepared from the composition provided by the invention has better clarification effect, light transmittance and lower melting temperature, and can reduce energy consumption and improve production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic glass, and in particular to a composition for photovoltaic glass, photovoltaic glass, and a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous exploration and research of photovoltaic glass production and manufacturing technology, photovoltaic glass production technology has been comprehensively improved. Clarifiers are substances that can vaporize or decompose at high temperatures to release gases to promote the discharge of bubbles in the glass liquid, which can effectively improve the quality of the glass.

[0003] According to the clarification mechanism, clarifiers can be divided into oxide clarifiers, sulfate clarifiers, halide clarifiers and composite clarifiers. Among them, composite clarifiers can give full play to the synergistic effect or superposition effect of each single clarifier, greatly enhancing the clarification ability. At present, they are widely used in the field of photovoltaic glass manufacturing, which has positive significance in reducing production costs and improving waste gas emissions.

[0004] However, in the glass manufacturing cost, composite clarifiers account for more than 12% of the company's raw material costs, and in order to accelerate the discharge of bubbles in the photovoltaic rolled glass liquid, it is necessary to increase the amount of composite clarifiers used and increase the melting temperature, which will increase energy consumption and increase manufacturing costs. Therefore, in order to increase corporate profits and market competitiveness and reduce production costs, there is an urgent need for updates and technological breakthroughs in the formulation of low-cost composite clarifiers.

[0005] CN117361873A discloses an ultra-white float glass, which is composed of SiO2: 70% to 72%, Al2O3: 1.0% to 4.5%, CaO: 8.0% to 9.0%, MgO: 3.5% to 5.0%, K2O: 0.5% to 1.5%, Na2O: 12% to 13%, Fe2O3: 0.0070% to 0.0100%; the amount of the composite clarifier is as follows: carbon powder 0.2% to 2.5%, sodium sulfate 1.0% to 2.5%, sodium nitrate 0.2% to 1.5%, sodium pyroantimonate 0.01% to 0.3%. The glass produced by this scheme has low transmittance and long glass liquid material properties, which is not suitable for photovoltaic glass rolling molding production. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of poor clarification effect and high melting temperature of photovoltaic glass in the prior art.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composition for photovoltaic glass, which contains 65-75wt% SiO2, 0.5-0.9wt% Al2O3, 13-15wt% Na2O, 0.02-0.2wt% K2O, 9-12wt% CaO, 2-5wt% MgO and 0.2-0.9wt% composite clarifier based on the total weight of the composition;

[0008] The content M1 of Na2O, the content M2 of K2O, the content M3 of SiO2 and the content M4 of Al2O3 satisfy equations (1) and (2) at the same time:

[0009] Formula (1): 0.035≤M4 / (M1+M2)≤0.065;

[0010] Formula (2): 69wt%≤M3+M4≤75.1wt%;

[0011] The composite clarifier is a combination of potassium bifluoride, potassium nitrate, sodium pyroantimonate, sodium sulfate and carbon powder.

[0012] Preferably, the content M1 of Na2O, the content M2 of K2O, the content M3 of SiO2 and the content M4 of Al2O3 satisfy formula (3) and formula (4) at the same time:

[0013] Formula (3): 0.045≤M4 / (M1+M2)≤0.0613;

[0014] Formula (4): 70.5wt%≤M3+M4≤72wt%.

[0015] Preferably, based on the total mass of the composite clarifier, the composite clarifier contains 5-15wt% potassium bifluoride, 1-11wt% potassium nitrate, 40-60wt% sodium pyroantimonate, 10-25wt% sodium sulfate and 1-5wt% carbon powder.

[0016] More preferably, based on the total mass of the composite clarifier, the composite clarifier contains 5-7wt% potassium bifluoride, 5-8wt% potassium nitrate, 58-60wt% sodium pyroantimonate, 20-25wt% sodium sulfate and 4-5wt% carbon powder.

[0017] Preferably, based on the total weight of the composition, the composition contains 70-71wt% SiO2, 0.7-0.9wt% Al2O3, 14-14.5wt% Na2O, 0.1-0.2wt% K2O, 9.5-10wt% CaO, 3.5-4wt% MgO, and 0.5-0.9wt% of a composite clarifier.

[0018] A second aspect of the present invention provides a method for preparing photovoltaic glass, the method using the composition for photovoltaic glass according to the first aspect, comprising:

[0019] (1) melting a mixture containing the composition for photovoltaic glass to obtain material I;

[0020] (2) clarifying and homogenizing the material I to obtain material II;

[0021] (3) subjecting the material II to a molding process to obtain a material III;

[0022] (4) Annealing the material III to obtain the photovoltaic glass.

[0023] Preferably, in step (1), the conditions of the melt treatment include: hot spot temperature of 1450-1500° C. and time of 3-6 h.

[0024] Preferably, in step (2), the conditions for the clarification and homogenization treatment include: a temperature of 1350-1450° C. and a time of 2-4 hours.

[0025] Preferably, in step (3), the forming process is carried out by calendering with a calendering roller;

[0026] The molding process conditions include: a temperature of 1100-1200°C.

[0027] Preferably, in step (4), the annealing treatment conditions include: temperature of 70-560° C. and time of 1-2 h.

[0028] The third aspect of the present invention provides photovoltaic glass prepared by the method described in the second aspect.

[0029] Preferably, based on the total mass of the photovoltaic glass, the amount of Fe2O3 introduced into the photovoltaic glass is not higher than 120 ppm.

[0030] The fourth aspect of the present invention provides the use of the composition for photovoltaic glass described in the first aspect and the photovoltaic glass described in the third aspect in solar photovoltaic power generation and / or solar thermal components.

[0031] The present invention can improve the clarification effect of photovoltaic glass and reduce the melting temperature of glass by precisely controlling the ratio of SiO2, Al2O3, CaO, MgO, K2O and Na2O and compounding a specific type of composite clarifier (a combination of potassium bifluoride, potassium nitrate, sodium pyroantimonate, sodium sulfate and carbon powder), while also improving the transmittance of glass. DETAILED DESCRIPTION

[0032] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0033] As mentioned above, the first aspect of the present invention provides a composition for photovoltaic glass, which contains 65-75wt% SiO2, 0.5-0.9wt% Al2O3, 13-15wt% Na2O, 0.02-0.2wt% K2O, 9-12wt% CaO, 2-5wt% MgO and 0.2-0.9wt% composite clarifier based on the total weight of the composition;

[0034] The content M1 of Na2O, the content M2 of K2O, the content M3 of SiO2 and the content M4 of Al2O3 satisfy equations (1) and (2) at the same time:

[0035] Formula (1): 0.035≤M4 / (M1+M2)≤0.065;

[0036] Formula (2): 69wt%≤M3+M4≤75.1wt%;

[0037] The composite clarifier is a combination of potassium bifluoride, potassium nitrate, sodium pyroantimonate, sodium sulfate and carbon powder.

[0038] It should be noted that the unit of M1, M2, M3, and M4 in formula (1) and formula (2) is wt%.

[0039] The inventors of the present invention have limited the content range of each component of the composition for photovoltaic glass provided by the present invention based on the following considerations:

[0040] When SiO2 is a glass network former and its content is too low, the chemical stability of the obtained glass substrate, especially the acid resistance, deteriorates; when the SiO2 content is too high, the high temperature viscosity of the obtained glass substrate increases greatly, making the melting property of the glass component deteriorate. Therefore, the inventors of the present invention limit the content of SiO2 to 65-75wt% after a lot of research. Exemplarily, in some examples, the content of SiO2 can be 65wt%, 65.6wt%, 67wt%, 69wt%, 69wt%, 70wt%, 71wt%, 72.5wt%, 73.5wt%, 75wt%.

[0041] As an intermediate oxide, Al2O3 has two typical structural units in glass, namely aluminum tetrahedron [A1O4] and aluminum oxide octahedron [AlO6]. When the Al2O3 content is too high, the melting point in glass production will increase and more stripe defects will appear. In order to obtain photovoltaic glass with low melting temperature and high transmittance performance, the inventors of the present invention have limited the content of Al2O3 to 0.5-0.9wt% after extensive research. Exemplarily, in some examples, the content of Al2O3 can be 0.5wt%, 0.55wt%, 0.6wt%, 0.65wt%, 0.7wt%, 0.75wt%, 0.8wt%, 0.85wt%, 0.9wt%.

[0042] Na2O is mainly used as a flux. It usually exists in the form of network exosome ions in glass, which can reduce the melting temperature of glass and promote the formation of glass. When its content is too low, it is easy to cause the melting temperature of glass to be high, and it is not easy to melt, which will cause the inhomogeneity of glass, thereby affecting the transmittance of glass; when the content of Na2O is too high, it can destroy the continuity of the glass network structure, increase the defects and pores in the glass, and these defects and pores can become channels for acidic medium erosion, thereby reducing the acid resistance of glass. Therefore, the inventors of the present invention have limited the content of Na2O to 13-15wt% after a lot of research. Exemplarily, in some examples, the content of Na2O can be 13wt%, 13.7wt%, 14.0wt%, 14.5wt%, 15wt%.

[0043] CaO exists as a network exosome ion, Ca 2+ It has the function of polarizing bridging oxygen and weakening silicon-oxygen bonds, which is one of the main reasons for reducing the high-temperature viscosity of glass. When its content is too low, it is easy to cause the high-temperature viscosity of the glass to be high and difficult to clarify and homogenize; when the CaO content is too high, it will generally make the material of the glass shorter and more brittle, and increase the tendency of glass crystallization, which is related to the CaO content. 2+ Therefore, after extensive research, the inventors of the present invention limit the content of CaO to 9-12wt%. Exemplarily, in some examples, the content of CaO can be 9.0wt%, 9.5wt%, 9.8wt%, 10.0wt%, 10.5wt%, 10.8wt%, 11.0wt%, 11.5wt%, 11.8wt%, 12.0wt%.

[0044] MgO, as a metal network exosome, can slow down the hardening speed of glass, improve the forming performance of glass, reduce the crystallization ability of glass and adjust the glass material. When its content is too low, it is easy to cause the glass material to be short and difficult to form, affecting the homogenization effect of glass, thereby affecting the transmittance; when the MgO content is too high, it will cause the glass to form a magnesium silicate film on the surface of the glass under the action of water and alkaline solution, which will peel off and enter the solution under certain conditions, and it is easy to produce delamination, so its usage should be strictly controlled. Therefore, the inventor of the present invention has limited the content of MgO to 2-5wt% after a lot of research. Exemplarily, in some examples, the content of MgO can be 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%.

[0045] In addition, the inventors of the present invention have also found through creative research that when the contents of the components satisfy both formula (1) and formula (2), and a composite clarifier consisting of potassium bifluoride, potassium nitrate, sodium pyroantimonate, sodium sulfate and carbon powder is compounded at the same time, the clarification effect and light transmittance of the glass can be significantly improved.

[0046] Preferably, the content M1 of Na2O, the content M2 of K2O, the content M3 of SiO2 and the content M4 of Al2O3 satisfy formula (3) and formula (4) at the same time:

[0047] Formula (3): 0.045≤M4 / (M1+M2)≤0.0613;

[0048] Formula (4): 70.5wt%≤M3+M4≤72wt%.

[0049] The inventors found that under this preferred specific embodiment, the photovoltaic glass provided by the present invention has better clarification effect, better light transmittance and lower melting temperature.

[0050] Preferably, based on the total mass of the composite clarifier, the composite clarifier contains 5-15wt% potassium bifluoride, 1-11wt% potassium nitrate, 40-60wt% sodium pyroantimonate, 10-25wt% sodium sulfate and 1-5wt% carbon powder.

[0051] More preferably, based on the total mass of the composite clarifier, the composite clarifier contains 5-7wt% potassium bifluoride, 5-8wt% potassium nitrate, 58-60wt% sodium pyroantimonate, 20-25wt% sodium sulfate and 4-5wt% carbon powder. The inventors found that under this preferred embodiment, the photovoltaic glass provided by the present invention has better clarification effect and light transmittance.

[0052] According to a specific preferred embodiment, the composite clarifier is prepared by the following steps:

[0053] S1: first mixing sodium pyroantimonate and sodium sulfate to obtain a mixture I; and

[0054] Mixing potassium bifluoride, potassium nitrate and carbon powder for a second time to obtain a mixture II;

[0055] S2: performing a third mixing of the mixture I and the mixture II to obtain the composite clarifier.

[0056] The inventors have found that the composite clarifier obtained under the above preferred embodiment has better stability and clarification effect.

[0057] It should be noted that, in the present invention, there is no particular requirement for the conditions of the first mixing, the second mixing and the third mixing, as long as uniform mixing is achieved. The present invention will not be described in detail here, and those skilled in the art should not understand this as a limitation of the present invention.

[0058] Preferably, based on the total weight of the composition, the composition contains 70-71wt% SiO2, 0.7-0.9wt% Al2O3, 14-14.5wt% Na2O, 0.1-0.2wt% K2O, 9.5-10wt% CaO, 3.5-4wt% MgO, and 0.5-0.9wt% composite clarifier. The inventors have found that under this preferred embodiment, the photovoltaic glass provided by the present invention has better clarification effect, light transmittance and lower melting temperature.

[0059] As mentioned above, the second aspect of the present invention provides a method for preparing photovoltaic glass, which uses the composition for photovoltaic glass according to the first aspect, comprising:

[0060] (1) melting a mixture containing the composition for photovoltaic glass to obtain material I;

[0061] (2) clarifying and homogenizing the material I to obtain material II;

[0062] (3) subjecting the material II to a molding process to obtain a material III;

[0063] (4) Annealing the material III to obtain the photovoltaic glass.

[0064] Preferably, in step (1), the conditions of the melt treatment include: hot spot temperature of 1450-1500° C. and time of 3-6 h.

[0065] In the present invention, the melting process is carried out in a glass melting furnace, and the glass melting furnace is selected from a flame furnace and / or an all-electric furnace.

[0066] Preferably, in step (2), the conditions for the clarification and homogenization treatment include: a temperature of 1350-1450° C. and a time of 2-4 hours.

[0067] Preferably, in step (3), the forming process is carried out by calendering with a calendering roller;

[0068] The molding process conditions include: a temperature of 1100-1200°C.

[0069] In the present invention, there is no special requirement for the specific operation steps of the forming process, which can be carried out according to conventional methods in the art as long as a glass plate meeting the size requirements can be obtained. The present invention will not elaborate on them here and should not be construed as a limitation to the present invention.

[0070] Preferably, in step (4), the annealing treatment conditions include: temperature of 70-560° C. and time of 1-2 h.

[0071] In the present invention, the annealing treatment is performed in an annealing furnace.

[0072] It should be noted that in the method for preparing photovoltaic glass of the present invention, SiO2, Al2O3, MgO, CaO, Na2O, and K2O can be selected from Si-containing compounds, Al-containing compounds, Mg-containing chemicals, Ca-containing compounds, Na-containing compounds, and K-containing compounds, respectively, and illustratively, they can be carbonates, nitrates, and / or oxides, and their amounts are calculated based on the oxides of the above elements. The present invention will not be elaborated here, and those skilled in the art should not be understood as limiting the present invention.

[0073] As mentioned above, the third aspect of the present invention provides photovoltaic glass prepared by the method described in the second aspect.

[0074] Preferably, based on the total mass of the photovoltaic glass, the amount of Fe2O3 introduced into the photovoltaic glass is not higher than 120 ppm.

[0075] In the present invention, the amount of Fe2O3 introduced can be controlled by controlling the content of iron impurities in the raw materials and avoiding the introduction of iron during production, and the implementation of iron removal measures is strengthened to ensure that the iron content is within the control range.

[0076] As mentioned above, the fourth aspect of the present invention provides the use of the composition for photovoltaic glass described in the first aspect and the photovoltaic glass described in the third aspect in solar photovoltaic power generation and / or solar thermal components.

[0077] The present invention will be described in detail below through examples.

[0078] In the following examples, unless otherwise specified, all raw materials used were commercially available.

[0079] In the following examples, unless otherwise specified, each wt% represents 100 g.

[0080] In the following examples, the performance testing methods involved are as follows:

[0081] Transmittance: tested by visible UV spectrophotometer (size: 100×100×2mm), wavelength range is 380nm-1100nm;

[0082] Quantification of bubble number: 100×100×2mm glass bubble number / piece, observe under a microscope, and count the number of bubbles with a diameter of more than 0.5mm.

[0083] Preparation Example 1

[0084] This preparation example is used to illustrate that the composite clarifier provided by the present invention is obtained by the following steps:

[0085] S1: first mixing sodium pyroantimonate and sodium sulfate to obtain a mixture I; and

[0086] Mixing potassium bifluoride, potassium nitrate and carbon powder for a second time to obtain a mixture II;

[0087] S2: performing a third mixing of the mixture I and the mixture II to obtain the composite clarifier Z1.

[0088] The conditions for the first mixing, the second mixing and the third mixing are all: stirring speed of 30 rpm, time of 20 min, and temperature of 25°C.

[0089] Based on the total mass of the composite clarifier, the amount of potassium bifluoride is 7wt%, the amount of potassium nitrate is 8wt%, the amount of sodium pyroantimonate is 60wt%, the amount of sodium sulfate is 20wt%, and the amount of carbon powder is 5wt%.

[0090] Preparation Example 2

[0091] This preparation example adopts a process similar to that of Preparation Example 1, except that the total mass of the composite clarifier in this preparation example is controlled the same as that in Preparation Example 1, but based on the total mass of the composite clarifier, the amount of potassium bifluoride is 6wt%, the amount of potassium nitrate is 7wt%, the amount of sodium pyroantimonate is 58wt%, the amount of sodium sulfate is 25wt%, and the amount of carbon powder is 4wt%.

[0092] The rest is the same as Preparation Example 1.

[0093] The composite clarifier Z2 was prepared.

[0094] Preparation Example 3

[0095] This preparation example adopts a process similar to that of Preparation Example 1, except that the total mass of the composite clarifier in this preparation example is controlled the same as that in Preparation Example 1, but based on the total mass of the composite clarifier, the amount of potassium bifluoride is 8wt%, the amount of potassium nitrate is 11wt%, the amount of sodium pyroantimonate is 58wt%, the amount of sodium sulfate is 20wt%, and the amount of carbon powder is 3wt%.

[0096] The rest is the same as Preparation Example 1.

[0097] The composite clarifier Z3 was prepared.

[0098] Preparation Example 4

[0099] This preparation example adopts a process similar to that of Preparation Example 1, except that potassium bifluoride is not used in this preparation example. The total mass of the composite clarifier controlled in this preparation example is the same as that in Preparation Example 1, but based on the total mass of the composite clarifier, the amount of potassium nitrate is 11wt%, the amount of sodium pyroantimonate is 60wt%, the amount of sodium sulfate is 25wt%, and the amount of carbon powder is 4wt%.

[0100] The rest is the same as Preparation Example 1.

[0101] The composite clarifier DZ4 was prepared.

[0102] Preparation Example 5

[0103] This preparation example adopts a process similar to that of Preparation Example 1, except that no carbon powder is used in this preparation example. The total mass of the composite clarifier controlled in this preparation example is the same as that in Preparation Example 1, but based on the total mass of the composite clarifier, the amount of potassium bifluoride is 8wt%, the amount of potassium nitrate is 7wt%, the amount of sodium pyroantimonate is 60wt%, and the amount of sodium sulfate is 25wt%.

[0104] The rest is the same as Preparation Example 1.

[0105] The composite clarifier DZ5 was prepared.

[0106] Example 1

[0107] This example is used to illustrate that the photovoltaic glass described in the present invention is prepared according to the formula in Table 1 and the method described below.

[0108] The method for preparing photovoltaic filter glass comprises the following steps:

[0109] (1) stirring and mixing the components in the photovoltaic glass composition uniformly, and then placing the components in a melting furnace for melting treatment to obtain material I; the melting treatment conditions are: hot spot temperature of 1450° C., and time of 4 hours;

[0110] (2) The material I is clarified and homogenized to obtain material II; the conditions of the clarification and homogenization treatment are: temperature of 1400° C. and time of 2 h.

[0111] (3) calendering the material II using a calendering roller to obtain material III; the calendering temperature is 1100° C.;

[0112] (4) Annealing the material III to obtain the photovoltaic glass. The annealing conditions are: temperature of 70-560° C. and time of 2 hours.

[0113] Unless otherwise specified, the remaining examples were carried out using a process similar to that of Example 1, except that the formulas and hot spot temperatures used in each example were different, as shown in Tables 1 and 2 for details.

[0114] Table 1

[0115]

[0116] Table 1 (Continued)

[0117]

[0118] Test Case

[0119] The above-mentioned test method was used to measure the performance of the photovoltaic glass obtained in each embodiment and comparative example. The specific results are shown in Table 2.

[0120] Table 2

[0121] Number of bubbles Light transmittance (%) Hot spot temperature (℃) Example 1 0 91.8 1450 Example 2 0 91.75 1480 Example 3 2 91.7 1500 Example 4 1 91.6 1500 Example 5 2 91.5 1480 Comparative Example 1 5 91.2 1480 Comparative Example 2 10 90.1 1580 Comparative Example 3 5 91.6 1500 Comparative Example 4 8 91.6 1500

[0122] It can be seen from the results in Table 2 that the formula provided by the present invention has a bubble number of ≤2, a transmittance of ≥91.5%, a good clarification effect, and a melting hotspot temperature of ≤1500°C. The lower melting temperature can reduce energy consumption and improve production efficiency.

[0123] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composition for photovoltaic glass, characterized in that: Based on the total weight of the composition, the composition contains 65-75wt% SiO2, 0.5-0.9wt% Al2O3, 13-15wt% Na2O, 0.02-0.2wt% K2O, 9-12wt% CaO, 2-5wt% MgO and 0.2-0.9wt% of a composite clarifier; The content M1 of Na2O, the content M2 of K2O, the content M3 of SiO2 and the content M4 of Al2O3 satisfy equations (1) and (2) at the same time: Formula (1): 0.035≤M4 / (M1+M2)≤0.065; Formula (2): 69wt%≤M3+M4≤75.1wt%; The composite clarifier is a combination of potassium bifluoride, potassium nitrate, sodium pyroantimonate, sodium sulfate and carbon powder.

2. The composition according to claim 1, characterized in that The content M1 of Na2O, the content M2 of K2O, the content M3 of SiO2 and the content M4 of Al2O3 satisfy equations (3) and (4) at the same time: Formula (3): 0.045≤M4 / (M1+M2)≤0.0613; Formula (4): 70.5wt%≤M3+M4≤72wt%.

3. The composition according to claim 1 or 2, characterized in that Based on the total mass of the composite clarifier, the composite clarifier contains 5-15wt% potassium bifluoride, 1-11wt% potassium nitrate, 40-60wt% sodium pyroantimonate, 10-25wt% sodium sulfate and 1-5wt% carbon powder; And / or, based on the total mass of the composite clarifier, the composite clarifier contains 5-7wt% potassium bifluoride, 5-8wt% potassium nitrate, 58-60wt% sodium pyroantimonate, 20-25wt% sodium sulfate and 4-5wt% carbon powder.

4. The composition according to claim 3, characterized in that Based on the total weight of the composition, the composition contains 70-71wt% SiO2, 0.7-0.9wt% Al2O3, 14-14.5wt% Na2O, 0.1-0.2wt% K2O, 9.5-10wt% CaO, 3.5-4wt% MgO, and 0.5-0.9wt% of a composite clarifier.

5. A method for preparing photovoltaic glass, characterized in that: The method uses the photovoltaic glass composition according to any one of claims 1 to 4, comprising: (1) melting a mixture containing the composition for photovoltaic glass to obtain material I; (2) clarifying and homogenizing the material I to obtain material II; (3) subjecting the material II to a molding process to obtain a material III; (4) Annealing the material III to obtain the photovoltaic glass.

6. The method according to claim 5, characterized in that In step (1), the conditions of the melt treatment include: hot spot temperature of 1450-1500°C and time of 3-6h.

7. The method according to claim 5 or 6, characterized in that: In step (2), the conditions for the clarification and homogenization treatment include: a temperature of 1350-1450° C. and a time of 2-4 hours.

8. The method according to any one of claims 5 to 7, characterized in that: In step (3), the forming process is carried out by calendering with a calendering roller; The conditions of the molding process include: a temperature of 1100-1200°C; And / or, in step (4), the annealing treatment conditions include: temperature of 70-560° C. and time of 1-2 h.

9. Photovoltaic glass prepared by the method according to any one of claims 5 to 8. Preferably, based on the total mass of the photovoltaic glass, the amount of Fe2O3 introduced into the photovoltaic glass is not higher than 120 ppm.

10. Use of the photovoltaic glass composition according to any one of claims 1 to 4 and the photovoltaic glass according to claim 9 in solar photovoltaic power generation and / or solar thermal components.

Citation Information

Patent Citations

  • Composite fluxing agent for clarifying waste glass

    CN102923945A

  • Ultra-clear glass formula

    CN104118988A

  • Novel composite clarifying agent applied to photovoltaic glass and application method of novel composite clarifying agent

    CN109516688A

  • Composite clarifying agent for producing ultra-white glass by float process

    CN109851216A

  • Glass clarifying agent and method for preparing ultra-high aluminosilicate cover plate glass by using same

    CN112624603A

Cited By

  • Photovoltaic glass anti-reflection strengthening preparation method based on micro-nano structure compression molding

    CN121135132A